Pengaruh Media Visualisasi Infografis Berbasis Coreldraw untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran Desain Grafis Kelas X RPL di SMK Pertiwi Kuningan - Arsyad, Firdaus; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to determine the effect of using infographic visualization media based on CorelDRAW on improving students' understanding in the subject of Graphic Design class X RPL at SMK Pertiwi Kuningan. The research method used was a quantitative method with a pre-test - post-test control design. The population of the study consisted of students of class X RPL. The sample used in this study was students of class X RPL 3 with a total of 36 students, and the sampling technique used was purposive sampling. Data collection techniques were carried out through observation, test techniques, and questionnaires. The data analysis technique in this study was normality test, homogeneity test, and hypothesis testing (T-Test). The results of the study showed an increase in students' understanding after using infographic visualization media based on CorelDRAW. Based on the calculation of hypothesis testing (t-test), it was known that the average post-test score was 85.00, while the pre-test score was 70.00, so it was known that the post-test score was higher than the pre-test score. It was also known that the t-count value was 1.906, and the t-table value was 1.688. Therefore, it can be concluded that t-count > t-table (1.906 > 1.688) and the significance value was less than 0.05 (p = 0.000 < 0.05), so it can be stated that there was a significant difference in the increase in learning outcomes between the pre-test and post-test scores. Thus, it can be concluded that H0 was rejected and Ha was accepted.